(untitled) (Journal of Applied Oral Science, 2022)
Objective: The aim of this study is to test, in vitro, the anti-cariogenic effect of experimental hybrid coatings, with nano clays of halloysite or bentonite, loaded with sodium fluoride or with a combination of sodium fluoride and stannous chloride, respectively. Methodology: The varnish Fluor Protector (1,000 ppm of F-) was used as positive control and no treatment was the negative control. Enamel specimens (5 mm × 5 mm) were obtained from bovine teeth. The specimens (n=10) had their surfaces divided into two halves (5 mm × 2.5 mm each), in which one half received one of the treatments (Hybrid; Hybrid + NaF; Hybrid + NaF + SnCl2; Hybrid + NaF Loaded; Hybrid + NaF + SnCl2 Loaded). The specimens were submitted to a cariogenic challenge using a biofilm model (S. mutans UA159, for 5 days). Enamel surfaces both under and adjacent to the treated area were analyzed for mineral loss and lesion depth, by transverse microradiography. The pH of the medium was measured twice a day, and the fluoride release was analyzed. Additional specimens were submitted to confocal analysis. Results: Data were statistically analyzed by two-way ANOVA followed by Tukey test (α=0.05). None of hybrid groups were able to reduce the lesion depth; the Hybrid + NaF group, however, was able to reduce mineral loss differing from the negative control (p=0.008). The groups showed no significant difference in the pH measurement and fluoride release. Confocal analysis confirmed that for all groups the biofilm growth was similar. Conclusion: None of the hybrid groups reduced lesion depth, but the Hybrid + NaF group was able to promote protection against mineral loss.